2023
DOI: 10.3389/fpsyt.2023.1129794
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and mental distress after COVID-19 testing. Prospective long-term analysis in a Viennese cohort

Abstract: BackgroundSymptoms of mental stress are a hallmark of the COVID-19 pandemic. We hypothesized that just testing for COVID-19 could act as an effective stressor for persisting symptoms of mental distress including posttraumatic stress disorder. Our study aimed to determine whether personal beliefs on individual control and competence (locus of control, LoC) correlate with symptoms of mental distress and positive screening for post-traumatic stress disorder during a 9-month observational period.MethodsBetween Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…It has been observed that people with positive personality traits have regulated stress even after testing positive for COVID-19, whereas people with negative traits suffered from a stress surge when testing positive for COVID-19. [26] Psychology Personality traits are the psychological faculties of an individual.…”
Section: Medicinementioning
confidence: 99%
“…It has been observed that people with positive personality traits have regulated stress even after testing positive for COVID-19, whereas people with negative traits suffered from a stress surge when testing positive for COVID-19. [26] Psychology Personality traits are the psychological faculties of an individual.…”
Section: Medicinementioning
confidence: 99%